Sustainable firm performance through top management team diversity - Mohd Salleh, Sri Sarah Maznah; Yusoff, Rushami Zien; Saad, Rohaizah (International Academic Research Journal, 2015)
The integration of various resources within the Top Management Team through diversity is one of the important aspects to enhance the firm performance.Besides, the importance of environmental and social concern has been recognized in achieving sustainable firm performance.Previous scholars suggested that having a diverse TMT is beneficial to the firm and firm performance should be measured through financial, social and environmental aspect in order to achieve sustainable firm performance. Therefore, this study will investigate the influence level of different diversities within the TMT toward firm financial, social, and environmental performance.